Роль технических университетов в формировании интеллектуально-нравственного уровня инженерных кадров - Братута, Эдуард Георгиевич; Ильинский, А. И. (НТУ "ХПИ", 2010)
Positive influence of technical universities structure of higher education establishments on elite leadership is spirituality has been considered. It has been underlined that leading specialists of technical science ought to cooperate closely with those of pedagogical and psychological science
Role of technical university in formation of intellectual and moral development of engineering personnel
Keywords: формирование духовности; техническая элита; управление кадрами; гуманизация образования